Effects of Changing Weather, Oceanographic Conditions, and Land Uses on Spatio-Temporal Variation of Sedimentation Dynamics along Near-Shore Coral Reefs - Otaño-Cruz, Abimarie; Montañez-Acuña, Alfredo A.; Torres-López, Valeria; Hernández-Figueroa, Elix M.; Hernández-Delgado, Edwin A. (Frontiers in Marine Science, 2017)
Sedimentation is a critical threat to coral reefs worldwide. Major land use alteration at steep, highly erodible semi-arid islands accelerates the potential of soil erosion, runoff, and sedimentation stress to nearshore coral reefs during extreme rainfall events. The goal of this study was to assess spatio-temporal variation of sedimentation dynamics across nearshore coral reefs as a function of land use patterns, weather and oceanographic dynamics, to identify marine ecosystem conservation strategies. Sediment was collected at a distance gradient from shore at Bahia Tamarindo (BTA) and Punta Soldado (PSO) coral reefs at Culebra Island, Puerto Rico. Sediment texture and composition were analyzed by dry sieving and loss-on-ignition techniques, and were contrasted with environmental variables for the research period (February 2014 to April 2015). Rainfall and oceanographic data were analyzed to address their potential role on affecting sediment distribution with BEST BIO-ENV, RELATE correlation, and linear regression analysis. A significant difference in sedimentation rate was observed by time and distance from shore (PERMANOVA, p<0.0100), mostly attributed to higher sediment exposure at reef zones closer to shore due to strong relationships with coastal runoff. Sedimentation rate positively correlated with strong rainfall events (Rho= 0.301, p=0.0400) associated with storms and rainfall intensity exceeding 15 mm/hr. At BTA, sediment deposited were mostly composed of sand, suggesting a potential influence of resuspension produced by waves and swells. In contrast, PSO sediments were mostly composed of silt-clay and terrigenous material, mainly attributed to a deforestation event that occurred at adjacent steep sub-watershed during the study period. Spatial and temporal variation of sedimentation pulses and terrigenous sediment input implies that coral reefs exposure to sediment stress is determined by local land use patterns, weather, and oceanographic dynamics. Comprehensive understanding of sediment dynamics and coastal ecosystem interconnectivity is fundamental to implement integrated and adaptive management strategies aimed to promote sustainable development at watershed and island wide-scale to fully mitigate terrigenous sediment impact to marine ecosystems. Furthermore, decision-making processes and policy needs to address sedimentation stress in the context of future climate to reduce land-based threats and strengthen coral reef resilience.